Pemberdayaan Pemuda Melalui Literasi Pangan dan Pertanian Berkelanjutan Menuju Desa Mandiri Pangan Ramah Lingkungan - Makmur, Muhammad Hadi; Eriyanti, Linda Dwi; Mubarok, Ahmad Munif; Bharata, Lukman Wijaya (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Arjasa Village, Jember Regency, is an independent village with the main potential in the agricultural sector but faces various social and economic challenges. As many as 33% of the population is aged 15-35 years, but the unemployment rate reaches 21%, with 22.5% of families still dependent on social assistance. Most of the population works in the agricultural sector (52.6%), but the majority (62.7%) are farm laborers with limited access to land ownership. In addition, the achievement of the village's SDGs, especially in the aspects of Zero Hunger Villages (SDG 2), Environmentally Aware Villages (SDG 12), and Quality Village Education (SDG 4) is still relatively low. To overcome this challenge, the empowerment of village youth communities through sustainable food and agriculture literacy to realize zero hunger and environmentally aware villages program is designed to increase youth's awareness, skills, and participation in sustainable agriculture and community-based food processing. This program is implemented with a phased approach, starting with strengthening human resources, socialization, implementation, and mentoring. The activities include sustainable agriculture training, agricultural product processing workshops, the formation of youth farmer groups, and the development of community reading gardens to improve food and agricultural literacy. With this program, village youth can act as agents of change in realizing food independent, environmentally friendly, and prosperous villages.